A WebQuest for Teaching Mathematics: Contributions to a Web Curriculum (Interdisciplinary Studies Journal, 2021)
This study explored the challenges and potential of developing webquests for building a web curriculum. Its objectives were: to understand the contemporary challenges in constructing a web curriculum; to describe the necessary steps for developing a webquest; to analyze the limitations of developing such a resource; and to evaluate its contributions to prospective scenarios. For this, a theoretical-bibliographical study was conducted on the didactic-pedagogical implications of social practices mediated by internet interfaces; the elements that underpin and allow the development of a webquest were described; a mathematics teaching proposal based on the use of a webquest was presented; and the limitations and potentialities of this methodological strategy for building a web curriculum were highlighted. As a product, a teaching sequence focused on spatial geometry was shared with the academic community, centered on the use of a webquest. The teaching sequence presented can be adapted to various contexts and degree programs, as well as to teachers already working in educational settings.
Keywords: Webquest; Mathematics Education; Web curriculum